Growth dynamics and sectoral instability in livestock and poultry: a policy-centric analysis with focus on Maharashtra - Ponnaganti Navyasree; Nobin Chandra Paul; K. Ravi Kumar; Dhananjay D. Nangare; S. A. Kochewad; K. Sammi Reddy (Discover Agriculture)
Abstract The livestock and poultry sectors play a crucial role in the agricultural economy contributing significantly to rural livelihoods, nutrition, and food security. This study assessed the growth dynamics and instability of livestock and poultry populations in India and Maharashtra from 1961 to 2019, employing a quantitative descriptive approach. Secondary data were sourced from quinquennial livestock censuses conducted by the Department of Animal Husbandry and Dairying, Government of India, with district-specific data from Department of Animal Husbandry, Government of Maharashtra to validate regional disparities within the state. The Compound Annual Growth Rate (CAGR) was calculated to evaluate long-term growth rates, while the Cuddy-Della Valle Instability Index (CDVI) was applied to measure population variability, correcting for trend components. The findings revealed a CAGR of 5.09% for Buffalo in Maharashtra, slightly lower than the national average of 6.53%, highlighting regional disparities in growth dynamics. The poultry sector shows remarkable growth in both Maharashtra (17.63%) and India (18.23%), driven by rising demand for poultry products and government initiatives. The CDVI reveals significant variability in livestock species, with Maharashtra exhibiting a higher overall instability index (9.88%) compared to the national level (3.77%), reflecting greater susceptibility to climatic, economic, and infrastructural challenges. These trends underscore the necessity for region-specific policy measures, such as promoting climate-resilient livestock breeds, enhancing fodder and water resources, bolstering veterinary services and market linkages to promote sustainable practices. The outcomes of this study furnish valuable information for policymakers and stakeholders to refine livestock and poultry management strategies, enhance productivity, reduce volatility and increase the income of the farmers, thereby ensuring resilience and food security in the state.